Exploring Geragogy as A Non-Formal Education Approach to Promote Quality of Life for The Elderly - Hestyan, Alvian Pramadani; Mardliyah, Sjafiatul; Susanto, Shobri Firman (PT ARRUS Intelektual Indonesia, 2025)
The ageing process often brings challenges in physical, psychological and social aspects that can affect the quality of life of the elderly. Non-formal education with a geragogy approach offers a significant solution to improve the quality of life of older people through learning. This article uses the literature review method to explore the concept, relevance, benefits and challenges in the application of geragogy to promote the quality of life of the elderly. The results show that the geragogy approach can reduce social isolation, improve cognitive capacity, and empower older adults socially and psychologically. However, geragogy implementation faces challenges such as financial barriers, age discrimination, and limited programme evaluation. This research highlights the importance of policy support and inclusive learning environments to maximise the positive impact of geragogy in improving the quality of life of older adults.